R/G Value—A Numeric Index of Individual Periodontal Health and Oral Microbiome Dynamics - Najmanova, Lucie; Sabova, Lenka; Lenartova, Magdalena; Janatova, Tatjana; Mysak, Jaroslav; Vetrovsky, Tomas; Tesinska, Barbora; Balikova Novotna, Gabriela; Koberska, Marketa; Broukal, Zdenek; Duskova, Jana; Podzimek, Stepan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The dysbiosis of oral microbiom (OM) precedes the clinical signs of periodontal disease. Its simple measure thus could indicate individuals at risk of periodontitis development; however, such a tool is still missing. Up to now, numerous microbial taxa were associated with periodontal health or periodontitis. The outputs of most studies could, nevertheless, be slightly biased from following two reasons: First, the healthy group is often characterized only by the absence of the disease, but the individuals could already suffer from dysbiosis without any visible signs. Second, the healthy/diseased OM characteristics are frequently determined based on average data obtained for whole groups of periodontally healthy persons versus patients. Especially in smaller sets of tested individuals the typical individual variability can thus complicate the unambiguous assignment of oral taxa to respective state of health. In this work the taxonomic composition of OM was evaluated for twenty periodontally healthy individuals and fifteen patients with chronic periodontitis. The narrowed selection set of the most diseased patients (confirmed by clinical parameters) and the most distant group of healthy individuals with the lowest probability of dysbiosis was determined by clustering analysis and used for the identification of marker taxa. Based on their representation in each individual oral cavity, we proposed the numeric index of periodontal health called R/G value. Its diagnostic potential was further confirmed using an independent set of twenty periodontally healthy individuals and twenty patients with periodontitis with 95 percent of samples assigned correctly. We also assessed the individual temporal OM dynamics in periodontal health and we compared it to periodontitis. We revealed that the taxonomic composition of the system changes dynamically but generally it ranges within values typical for periodontal health or transient state, but far from values typical for periodontitis. R/G value tool, formulated from individually evaluated data, allowed us to arrange individual OMs into a continuous series, instead of two distinct groups, thus mimicking the gradual transformation of a virtual person from periodontal health to disease. The application of R/G value index thus represents a very promising diagnostic tool for early prediction of persons at risk of developing periodontal disease.